ANALISIS KUAT TEKAN BETON MENGGUNAKAN AGREGAT HALUS PASIR PANTAI JAWAI DAN AGREGAT KASAR BATU PECAH DI KABUPATEN SAMBAS KALIMANTAN BARAT: ANALISIS KUAT TEKAN BETON MENGGUNAKAN AGREGAT HALUS PASIR PANTAI JAWAI DAN AGREGAT KASAR BATU PECAH DI KABUPATEN SAMBAS KALIMANTAN BARAT - teguh, angga; Rusfiandi, wandi; rachmadi, rizul (RETENSI, 2022)
Concrete is a composite material (mixture) of several materials whose basic binder consists of acombination of fine aggregate, coarse aggregate, water and different additives in a particular mixture. Sandis a filler material that is used with a binder and water to form a dense and hard mixture. The beach sand inthe Jawai District, Sambas Regency has the potential because of its availability in large quantities, namely42.53 km long, quite a lot of sandy beaches and rocks in the hills of Ramayadi Village.This study aims to compare and determine the value of the compressive strength of concrete producedfrom concrete using beach sand as a substitute for fine aggregate that is treated (washed and not washed) andby using coarse aggregate in the form of crushed stone from the South Jawai District, Sambas Regency. Theresearch was conducted on cube specimens measuring 15 cm long, 15 cm wide and 15 cm high.The tests carried out were testing the compressive strength of concrete at the age of 7 days and 14days. The test results at the age of 7 days for unwashed beach sand and washed beach sand respectivelyshowed an average compressive strength of 114.0514 kg/cm2 and 153.9535 kg/cm2. While the test results atthe age of 14 days for unwashed beach sand and washed beach sand respectively showed an averagecompressive strength of 142.6046 kg/cm2 and 209.8392 kg/cm2.